2010
DOI: 10.5293/ijfms.2010.3.1.029
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Modeling for Optimization of a Centrifugal Compressor Impeller

Abstract: This paper presents a procedure for the design optimization of a centrifugal compressor. The centrifugal compressor consists of a centrifugal impeller, vaneless diffuser and volute. And, optimization techniques based on the radial basis neural network method are used to optimize the impeller of a centrifugal compressor. The Latin-hypercube sampling of design-of-experiments is used to generate the thirty design points within design spaces. Three-dimensional Reynoldsaveraged Navier-Stokes equations with the shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…(Each design based on DOE had a different element size, even though the size factor was "1", owing to different geometries of the blade). An H/J/C/L grid hexahedral mesh type was used for the inducer (inlet), vaneless diffuser, and other regions, while the O-grid mesh type was used for the nearby LE and other blade surface regions [7,8] (Figure 5). Owing to periodicity, these meshes were applied only for one blade passage consisting of one main blade and one splitter blade to reduce computational time.…”
Section: Design Parameters Boundary Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…(Each design based on DOE had a different element size, even though the size factor was "1", owing to different geometries of the blade). An H/J/C/L grid hexahedral mesh type was used for the inducer (inlet), vaneless diffuser, and other regions, while the O-grid mesh type was used for the nearby LE and other blade surface regions [7,8] (Figure 5). Owing to periodicity, these meshes were applied only for one blade passage consisting of one main blade and one splitter blade to reduce computational time.…”
Section: Design Parameters Boundary Valuesmentioning
confidence: 99%
“…Thus, isentropic efficiency was improved by 1.8% considering optimization of the beta distribution on the main blade. The baseline and optimized impeller were compared at several off-design points [7,8]. To do so, flow simulations were carried out at an additional five mass flow rates for reference, and the optimized impeller and results are shown in Figure 12.…”
Section: Comparison Of the Baseline (Base Main-base Splitter) And Optmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a first approximation of the geometry of these components is parametrically generated and a relatively elaborate optimization process is carried out with the objective of attaining maximum efficiency within the selected parameterization, the assigned requirements and the relevant operational constraints. More recently, numerical optimization strategies based on the Radial Basis Neural Network (RBNN) have been applied by many researches 4,5,6,7,8 . Other systematic numerical optimization approaches are based on mean streamline flow analyses 9 , three-dimensional inverse methods coupled with optimization algorithms 10 , and numerical flow simulation 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Other objective functions are also used for optimization. For example, Kim et al [11] enhanced the total-to-total pressure ratio of an impeller with four design variables by constructing the curves of the shroud and the hub by Bezier curves. Samad et al [12] demonstrated the advantage of using multiple surrogates in the shape optimization of a transonic axial compressor blade and selected adiabatic efficiency, total pressure, and total temperature as objective functions.…”
Section: Introductionmentioning
confidence: 99%